Analisis SWOT: Faktor Internal dan Eksternal pada Pengembangan Usaha Agrowisata (Studi Kasus di Kopi Luwak Cikole, Kabupaten Bandung Barat) - Gessalofa, Rajasa; Turgarini, Dewi; Ningsih, Caria (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The West Bandung Regency is recognized as a prominent tourism destination, with a geographical setting highly conducive to agrotourism development. Among its attractions, Kopi Luwak Cikole stands out for its unique product offerings and the distinctive experiences it provides to visitors. By conducting a SWOT analysis, this research aims to facilitate the development of Kopi Luwak Cikole as an agrotourism destination. The objective is to identify the internal and external factors influencing its growth in the West Bandung Regency. Employing a qualitative method with a case study approach, data processing involves Internal Factor Environment (IFE) analysis to pinpoint strengths to leverage and weaknesses to address, along with External Factor Environment (EFE) analysis to identify opportunities to exploit and threats to mitigate. The scores derived from the IFE and EFE matrices are analyzed and categorized, resulting in an internal factor score of 2.84 and an external factor score of 2.9. Both scores exceed the threshold of 2.5, indicating that the company is in a robust internal and external position. Consequently, the company demonstrates above-average capabilities to capitalize on strengths and opportunities, rectify weaknesses, and proactively address potential threats.